2013
DOI: 10.1016/j.jacc.2013.01.074
|View full text |Cite
|
Sign up to set email alerts
|

Increased 99mTc-Sestamibi Washout Reflects Impaired Myocardial Contractile and Relaxation Reserve During Dobutamine Stress Due to Mitochondrial Dysfunction in Dilated Cardiomyopathy Patients

Abstract: Increased (99m)Tc-MIBI washout may predict mitochondrial dysfunction and the impairment of myocardial contractile and relaxation reserves during dobutamine stress in DCM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 26 publications
1
35
0
9
Order By: Relevance
“…99m Tc-MIBI imaging is now accepted as an indicator of radiopharmaceutical accumulation in mitochondria [4][5][6][7][8][9][10][11][12] . However, there is no generally accepted standardized method for measuring mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…99m Tc-MIBI imaging is now accepted as an indicator of radiopharmaceutical accumulation in mitochondria [4][5][6][7][8][9][10][11][12] . However, there is no generally accepted standardized method for measuring mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…Kawamoto et al reported decreased retention of 99m Tc-MIBI in the hearts of patients with heart failure, which is associated with decreased mitochondrial membrane potential 5) . Several studies have reported that decreased retention of 99m Tc-MIBI in the heart reflects impaired myocardial con-*Correspondence: shinjisato2005hawaii@yahoo.co.jp tractility due to mitochondrial dysfunction in patients with cardiomyopathy [6][7] . Moreover, Crane et al demonstrated that mitochondrial retention of 99m Tc-MIBI was not organ specific 7) .…”
Section: Introductionmentioning
confidence: 99%
“…Another potential mechanism that would explain why segments that are viable by 201Tl criteria do not respond to dobutamine relates to tethering of these segments to regions of extensive scar, which would inhibit recovery of systolic function after successful revascularization. Here, viability is not "overestimated" by 201Tl scintigraphy [53]. These tethered segments are indeed viable but cannot respond to an inotropic stimulus with enhanced regional thickening or wall motion.…”
mentioning
confidence: 74%
“…Thus, revascularization may not improve resting function in this situation compared with the situation of severe resting regional asynergy without extensive scar (hibernation) [53]. Another potential mechanism that would explain why segments that are viable by 201Tl criteria do not respond to dobutamine relates to tethering of these segments to regions of extensive scar, which would inhibit recovery of systolic function after successful revascularization.…”
mentioning
confidence: 99%
“…WR negatively correlated with LVEF (r 2 = 0.679). Hayashi and colleagues [27] added significant information to these observations. These investigators studied 20 patients with dilated cardiomyopathy (NYHA class I = 8, class II = 10 and class III = 2; mean LVEF = 33 %) divided into two groups on the basis of WR.…”
Section: Mitochondriamentioning
confidence: 97%